2012
DOI: 10.1088/0957-4484/23/41/415102
|View full text |Cite
|
Sign up to set email alerts
|

Cell membrane conformation at vertical nanowire array interface revealed by fluorescence imaging

Abstract: The perspectives offered by vertical arrays of nanowires for biosensing applications in living cells depend on the access of individual nanowires to the cell interior. Recent results on electrical access and molecular delivery suggest that direct access is not always obtained. Here, we present a generic approach to directly visualize the membrane conformation of living cells interfaced with nanowire arrays, with single nanowire resolution. The method combines confocal z-stack imaging with an optimized cell mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
136
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(143 citation statements)
references
References 22 publications
7
136
0
Order By: Relevance
“…The cells were then incubated with 5 μM fluorescent SNAP label (SNAP-Surface 549) for 5 minutes before being washed and fixed. The HEK/SNAP staining technique has previously been used to establish membrane continuity around nanofeatures17. All cells were imaged in PBS with confocal microscopy to isolate the basal membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The cells were then incubated with 5 μM fluorescent SNAP label (SNAP-Surface 549) for 5 minutes before being washed and fixed. The HEK/SNAP staining technique has previously been used to establish membrane continuity around nanofeatures17. All cells were imaged in PBS with confocal microscopy to isolate the basal membrane.…”
Section: Resultsmentioning
confidence: 99%
“…27−31 The PC-12 cells cultured on the VNEA were further characterized by z-step fluorescent scanning with two-photon microscopy ( Figure 2d). 19,32,33 The cross-sectional images (Figure 2e) clearly show that the cells invaginate the NW electrodes. We also observed several vertical NW electrode−cell interfaces by SEM and confirmed that the electrodes penetrate and locate inside of cytoplasm of the cells by the cross-sectional SEM image (Supporting Information, Figure S2).…”
Section: T He Ephaptic Interaction Between Living Cells and Electricalmentioning
confidence: 97%
“…Due to the high aspect ratio and the characteristic nanoscale dimensions, nanoneedles intimately contact large traits of the cell membrane, strongly interacting with it and with the intracellular milieu 16,37,38 ( Figure 2). It is this unique interaction, whose details are still largely unexplored, that enables their superior ability to investigate the intracellular space.…”
Section: The Biointerfacementioning
confidence: 99%